Chaveamento de pulsos ultracurtos em grades de Bragg não-lineares de fibras ópticas - Morais Neto, Apiano Ferreira de (2006)
Nonlinear fiber Bragg gratings has been considered since the end of last century for applications in optical communications and sensor techniques. The investigation of ultrashort pulses in linear Bragg gratings, however has been considered in the last few years due the development of specifical numerical techniques to solve this problem. In the present work an analytical and numerical study of the reflection and transmission characteristics of nonlinear Bragg gratings was done. For the first time, it has been considered periodic variations of the nonlinearity in that devices operating in the continuous wave regime, leading to a new class of nonuniform gratings. It was extensively investigated the bi- and multistable characteristics in these nonlinear fiber Bragg gratings. Also, for the first time, the numerical study of ultrahsort pulses (»1 ps) incident in nonlinear gratings was done. The focus was the input pulse intensity dependence on that gratings. Also, the depedences in the time shapes of grating index modulation depth and nonlinear index were studied. Apodized gratings were considered since they are of fundamental importance in modern communications systems.